Learning Application for Slow Learner Children Using Gamification Approach: Matematik Pintar - MOHD ZIN, SITI NUR SUWAIBAH; A Hamid, Rahayu (Applied Information Technology And Computer Science, 2024)
In this globalized era, learning using mobile devices has become a trend. Mobile devices have become a complete set of applications to help the education field. Additionally, gamification technology has been growing famous nowadays. Students can understand the learning better with the help of animation and gamification technology. Therefore, the contents of the learning application for slow learner children are developed using a gamification approach to present the learning materials. The methodology used in developing this proposed application is Multimedia Mobile Content Development (MMCD). The total of 31 respondents have performed user acceptance test. This application is to assist the user to learn about basic mathematics with the help of multimedia elements.